2020
DOI: 10.1021/acs.inorgchem.0c01318
|View full text |Cite
|
Sign up to set email alerts
|

Metallostar Assemblies Based on Dithiocarbamates for Use as MRI Contrast Agents

Abstract: Two different octadentate gadolinium chelates based on DO3A and DOTAGA chelates (hydration number q = 1) have been used to prepare a series of bi-, tri-and tetrametallic d-f mixed-metal complexes. The piperazine-based dithiocarbamate linker ensures that rotation of the gadolinium chelates is restricted, leading to enhanced relaxivity (r1) values, which increase with overall mass and the number of gadolinium units. The r1 value (at 10 MHz, 25 °C) per Gd unit rises from 5.0 mM −1 s −1 for the Gd-DO3A-NH2 monogad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Additionally, the increased rigidity helps minimize localized molecular motions which may reduce relaxation enhancement as observed in polymer and metallostar-based contrast agents. 46,47 The MOPs were synthesized with careful stochiometric control in methanol using six equivalents of ligand to four equivalents of trivalent metal salts. The Fe(III) reaction mixtures changed from a green to blue to deep red with increasing additions of KOH indicative of the formation of triscatecholate Fe(III) centers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the increased rigidity helps minimize localized molecular motions which may reduce relaxation enhancement as observed in polymer and metallostar-based contrast agents. 46,47 The MOPs were synthesized with careful stochiometric control in methanol using six equivalents of ligand to four equivalents of trivalent metal salts. The Fe(III) reaction mixtures changed from a green to blue to deep red with increasing additions of KOH indicative of the formation of triscatecholate Fe(III) centers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Rigidity in the catecholamide ligand is important to form discrete MOPs, as it prevents the ligand from chelating the same metal center with both catecholate donors. Additionally, the increased rigidity helps minimize localized molecular motions which may reduce relaxation enhancement as observed in polymer and metallo-star-based contrast agents. , …”
Section: Resultsmentioning
confidence: 99%
“…A ligand matching both criteria was a DOTA derivative, DOTAGA (GA for glutamic acid) . Reassuringly, studies have demonstrated the robust nature of Gd(III) complexes formed with this ligand, and no significant toxicity has been observed, even with compounds presenting multiple metal complexes …”
Section: Resultsmentioning
confidence: 98%
“…Cyclic disulfides, which form dithiolates on attachment to the surface [88], have also been applied as dithiocarbamates [89]. Dithiocarbamates have been shown to displace thiols on gold nanoparticle surfaces in a vigorous manner [90]. There are many chelators developed connecting Gd to AuNPs, but the cyclic 10-tetraacetic acid (DOTA) is preferred due to its kinetic inertness [91].…”
Section: Consolidation Of Gold and Gadolinium Nanoparticles 41 Applic...mentioning
confidence: 99%